Soccer passing accuracy differentiates between high and low digit ratio (2D:4D) soccer players - Shahidul Islam, M.; Kundu, B. (American Journal of Sports Science, 2020)
The purpose of the present study was to know soccer passing accuracy performances between the national youth level soccer players possessing high digit ratio and low digit ratio (2D:4D). The study was carried out in 108 male soccer players of Bangladesh aged between 16 to 19 years for measured the digit ratio. To find out the high and low digit ratio groups of participant quartile deviation has been used. Participants belonged to 0.973 and above (N=28) were categorized into high digit ratio group and 0.942 and below (N=28) were categorized into low digit ratio group. Soccer passing accuracy performance was assessed (N=56) by using Loughborough Soccer Passing Test (LSPT). Digit ratio (2D:4D) was measured by digital vernier caliper, Mitutoyo Corporation, Japan measuring to 0.01 mm. The length of the index finger (2D) and ring finger (4D) measured in millimeters from the second metacarpophalangeal crease of the finger to the fingertip. The mean digit ratio was calculated as dividing the length of the 2D by the length of the 4D for the left and right hand one by one and then computes the mean of these two ratios. To find out the significance of differences of soccer passing accuracy between the high digit ratio and the low digit ratio groups independent t-test was used. It was observed that the mean score in soccer passing accuracy performance, i.e., LSPT Total performance (TP) of the lower digit ratio, group was a significantly better performer than that of the high digit ratio group. A higher level of fetal testosterone, characterized by lower values of the digit finger ratio (2D:4D), may be associated with a higher performance of soccer passing accuracy in multifaceted aspects including passing, dribbling, controlling, turning, decision-making, and cognition.